A concise practical clinical guide to identifying spasticity in neurological shoulder dysfunction - Hoad, Damon; Ashford, Stephen; Bavikatte, Ganesh; Farrell, Rachel; Robertson, Adrian; Wissel, Jörg (Frontiers in Neurology, 2025)
BackgroundSpasticity is a known complication to the hemiplegic shoulder following acquired brain injury. However, there is a current discrepancy between the diagnosis of arm spasticity and the subsequent assessment and treatment of spasticity in people with shoulder involvement.ObjectiveAn expert panel aimed to establish a consensus and provide a simple structured approach to identifying and assessing people with spasticity of the hemiplegic shoulder.MethodsA consensus group of six spasticity experts were interviewed individually via 1-h video calls to ascertain how they assess people with arm spasticity for shoulder involvement. During an in-person meeting in March 2023, a consensus-building process was used to discuss four topics: a checklist/tool to identify shoulder involvement in upper limb spasticity, measurements/scales for assessing shoulder spasticity, ‘red flags’ for other conditions affecting the shoulder, and assessment limitations and practicalities.ResultsWhere there was full agreement on a topic, recommendations to overcome challenges for initial and ongoing assessment of shoulder spasticity and goal-setting were developed, and categorized as Posture, Purposeful activity and Pain (‘the three Ps’). Posture should be observed when sitting and walking, as appropriate for the person, and compared to published shoulder spasticity patterns. Purposeful activity should be assessed using a systematic approach. The presence and nature of shoulder pain should be ascertained. Recommendations on impairment- and function-related measures are given.ConclusionThis consensus guidance provides practical recommendations on identifying shoulder spasticity to support clinicians in their management of people with neurological shoulder dysfunction.